2003
DOI: 10.1103/physrevlett.91.261801
|View full text |Cite
|
Sign up to set email alerts
|

Evidence forB0π0π0

Abstract: We report evidence for the decay B0-->pi(0)pi(0). The analysis is based on a data sample of 152x10(6) BBmacr; pairs collected at the Upsilon(4S) resonance with the Belle detector at the KEKB e(+)e(-) storage ring. We detect a signal for B0-->pi(0)pi(0) with a significance of 3.4 standard deviations, and measure the branching fraction to be [1.7+/-0.6(stat)+/-0.2(syst)]x10(-6).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 173 publications
(58 citation statements)
references
References 23 publications
0
58
0
Order By: Relevance
“…The inputs to the network are (i) a Fisher discriminant [17] formed from modified Fox-Wolfram moments [18], (ii) the vertex separation between the B candidate and the remaining tracks, (iii) the cosine of the decay angle of D ! K þ À , where the decay angle is defined as the angle between the K þ candidate and the B À candidate in the rest frame of the D, (iv) the cosine of the angle between the B candidate and the beam axis in the e þ e À center-of-mass frame, (v) the expected B flavor dilution factor that ranges from zero for no flavor information to unity for unambiguous flavor assignment [19], (vi) the cosine of the angle between the thrust axis of the B candidate and that of the rest of the event, where the thrust axis is oriented in such a way that the sum of momentum projections is maximized, and four other variables that exploit the kinematics of the events.…”
mentioning
confidence: 99%
“…The inputs to the network are (i) a Fisher discriminant [17] formed from modified Fox-Wolfram moments [18], (ii) the vertex separation between the B candidate and the remaining tracks, (iii) the cosine of the decay angle of D ! K þ À , where the decay angle is defined as the angle between the K þ candidate and the B À candidate in the rest frame of the D, (iv) the cosine of the angle between the B candidate and the beam axis in the e þ e À center-of-mass frame, (v) the expected B flavor dilution factor that ranges from zero for no flavor information to unity for unambiguous flavor assignment [19], (vi) the cosine of the angle between the thrust axis of the B candidate and that of the rest of the event, where the thrust axis is oriented in such a way that the sum of momentum projections is maximized, and four other variables that exploit the kinematics of the events.…”
mentioning
confidence: 99%
“…To suppress the dominant e þ e − → qq ðq ∈ fu; d; s; cgÞ continuum background, we use a neural network based on four input variables calculated in the CM frame: (1) the cosine of the angle between the B momentum and the z axis, (2) the likelihood ratio of modified Fox-Wolfram moments [61,62] that gives the strongest separation power, (3) the cosine of the angle between the third sphericity axes [63] calculated from the B candidate and all other particles in the rest of the event (ROE), and (4) the cosine of the angle between the first sphericity axis in the ROE and the z axis. The network is trained with a GEANT3-based Monte Carlo (MC) simulation [64].…”
Section: Background Suppressionmentioning
confidence: 99%
“…Since d/L 0.4, in which d and L is the overall size of the NP and BCP domain spacing, respectively, it can be expected that the NPs are localized at the center of the PMMA domain, as theoretically predicted by Balazs and coworkers. 62 Therefore, it was concluded that the system was in non-equilibrium, trapped by a kinetic barrier formed by the rapid evaporation of solvent. Thus, to arrive at an equilibrium state the solvent was evaporated very slowly during the annealing process.…”
Section: Block Copolymer Thin Film With Inorganic Nanoparticlesmentioning
confidence: 99%